Dyspnea Secondary to Mediastinal Mass: A Rare Presentation of Metastatic Penile Squamous Cell Carcinoma - Stephanie Niforatos MD; Michael Sandhu MD; Alanna Siegenthaler MD; Jozsef Bordas MD; Taylor Loon MBBCh; Komal Akhtar MD (SAGE Publishing, 2023)
Penile squamous cell carcinoma is a rare diagnosis in the United States; however, the incidence is significantly higher in developing countries. This cancer is categorized into human papilloma virus (HPV)-associated and independent disease. In this article, we present a rare case of HPV-independent penile squamous cell carcinoma. Our patient was a 75-year-old Caucasian male who initially presented with a penile ulcer which was managed with partial penectomy and adjuvant chemotherapy. The patient was monitored on surveillance and did not pursue lymph node dissection. He was noted to have recurrence with metastatic disease 5 years after his initial presentation. Due to the aggressive nature of his disease, the patient was admitted to the hospital and treated with chemotherapy and immunotherapy.